1985
DOI: 10.1116/1.583264
|View full text |Cite
|
Sign up to set email alerts
|

Lithographic evaluation and processing of chlorinated polymethylstyrene

Abstract: Chlorinated polymethylstyrene has been shown to behave as a negative resist upon electron beam exposure. Polymethylstyrene was prepared by both anionic and free radical techniques and chlorinated to produce a series of polymers with a range from 0 to 2.5 chlorine atoms per polymer repeat unit (0 to 42.5 wt. % chlorine). Sensitivity and contrast were found to be a function of chlorine content, molecular weight, and polydispersity. Sensitivity was maximum for materials with 0.6 to 0.9 chlorine atoms per repeat u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…G= -0.414G~ = 0.399/D~ ~ 9 Mw [4] G= -0.250Gs = 0.241/Dn ~ " Mw [5] The data points are plotted in accordance with these equations in Fig. 6 and 7, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…G= -0.414G~ = 0.399/D~ ~ 9 Mw [4] G= -0.250Gs = 0.241/Dn ~ " Mw [5] The data points are plotted in accordance with these equations in Fig. 6 and 7, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…There have been several reports of halogenation of poly(4-MeSt) to introduce chloromethyl-or bromomethyl groups on to the rings. [19][20][21] Bromination reactions are, compared to chlorination reactions, highly selective toward formation of the monobromination of the methyl groups. Chung, et al reported the radical bromination of α-olefin/4-MeSt copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…this correction is that the apparent gel dose of the copolymer dg/d log 10 r=2.303 K ar e−ar (7) resists is marginally suppressed, an effect that can be attributed to the irregular distribution of crosslinking points along the By substituting r=R0.5, it follows that contrast is given by eqn. (8). polymer chain that results from a statistical copolymerisation process.…”
Section: Discussionmentioning
confidence: 99%